2012
DOI: 10.1002/hep.25643
|View full text |Cite
|
Sign up to set email alerts
|

Role of transcriptional and posttranscriptional regulation of methionine adenosyltransferases in liver cancer progression

Abstract: Down-regulation of the liver-specific MAT1A gene, encoding S-adenosylmethionine (SAM) synthesizing isozymes MATI/III, and up-regulation of widely expressed MAT2A, encoding MATII isozyme, known as MAT1A:MAT2A switch, occurs in hepatocellular carcinoma (HCC). Here we found Mat1A:Mat2A switch and low SAM levels, associated with CpG hypermethylation and histone H4 deacetylation of Mat1A promoter, and prevalent CpG hypomethylation and histone H4 acetylation in Mat2A promoter of fast-growing HCC of F344 rats, geneti… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

8
98
0

Year Published

2012
2012
2018
2018

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 75 publications
(106 citation statements)
references
References 42 publications
(72 reference statements)
8
98
0
Order By: Relevance
“…In both animal models and human HCC, decreased MAT1A expression correlates with more aggressive disease and worse prognosis (21). Consistent with an important role of MAT1A in HCC pathogenesis, mice deficient in Mat1a develop spontaneous HCC (7).…”
Section: Discussionmentioning
confidence: 96%
See 1 more Smart Citation
“…In both animal models and human HCC, decreased MAT1A expression correlates with more aggressive disease and worse prognosis (21). Consistent with an important role of MAT1A in HCC pathogenesis, mice deficient in Mat1a develop spontaneous HCC (7).…”
Section: Discussionmentioning
confidence: 96%
“…MAT1A is predominantly expressed in normal liver, and it is often silenced in human HCC (3,4,20,21). In both animal models and human HCC, decreased MAT1A expression correlates with more aggressive disease and worse prognosis (21).…”
Section: Discussionmentioning
confidence: 99%
“…It has been found that Mat1A:Mat2A switch and low SAM levels, associated with CpG hypermethylation of Mat1A promoter, and prevalent CpG hypomethylation in Mat2A promoter of fast growing HCC (Frau et al, 2012). Forced MAT1A overexpression in HepG2 and Huh7 cells led to rise in SAMe level, decreased cell proliferation, increased apoptosis (Li et al, 2010;Frau et al, 2012).…”
Section: Discussionmentioning
confidence: 99%
“…We found that 5-Aza-CdR inhibited the growth of Huh7 cells and induced apoptosis in Huh7 cells. Furthermore, We investigated 5-Aza-CdR induced apoptosis in Huh7 cells through down-regulation of Bcl-2, up-regulation of Bax and caspase-3, we inferred increased SAMe production by 5-Aza-CdR caused the result (Frau et al, 2012).…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation